On The Discrete Nature of The Gravitational Force (JOURNAL OF ADVANCES IN PHYSICS, 2018)
The standard model of particle physics has been extremely successful in unifying the strong, weak, and electromagnetic forces through the unitary product group SU(3) X SU(2) X U(1); and general relativity has been equally accurate in describing gravitation. No attempt thus far, however, has managed to incorporate general relativity into the standard model—or any other model. And while no attempt will, herein, be made to accomplish that endeavor, perhaps some of the insights will constitute a helpful step in that direction.  In the following pages, gravitation and electromagnetism are looked at in new and different ways.